The role of mesopelagic fishes as microplastics vectors across the deep-sea layers from the Southwestern Tropical Atlantic. (1st May 2022) - Justino, Anne K.S.; Ferreira, Guilherme V.B.; Schmidt, Natascha; Eduardo, Leandro N.; Fauvelle, Vincent; Lenoble, Véronique; Sempéré, Richard; Panagiotopoulos, Christos; Mincarone, Michael M.; Frédou, Thierry; Lucena-Frédou, Flávia
Abstract: Microplastics (MPs; <5 mm) are a macro issue recognised worldwide as a threat to biodiversity and ecosystems. Widely distributed in marine ecosystems, MPs have already been found in the deep-sea environment. However, there is little information on ecological mechanisms driving MP uptake by deep-sea species. For the first time, this study generates data on MP contamination in mesopelagic fishes from the Southwestern Tropical Atlantic (SWTA) to help understand the deep-sea contamination patterns. An alkaline digestion protocol was applied to extract MPs from the digestive tract of four mesopelagic fish species: Argyropelecus sladeni, Sternoptyx diaphana (Sternoptychidae), Diaphus brachycephalus, and Hygophum taaningi (Myctophidae). A total of 213 particles were recovered from 170 specimens, and MPs were found in 67% of the specimens. Fibres were the most common shape found in all species, whereas polyamide, polyethylene, and polyethylene terephthalate were the most frequent polymers. The most contaminated species was A. sladeni (93%), and the least contaminated was S. diaphana (45%). Interestingly, individuals caught in the lower mesopelagic zone (500–1000 m depth) were less contaminated with MPs than those captured in the upper mesopelagic layer (200–500 m). Our results highlight significant contamination levels and reveal the influence of mesopelagic fishes on MPs transport in the deep waters of the SWTA. Graphical abstract: Image 1 Highlights: Microplastics were found in deep-sea fishes from the Southwestern Tropical Atlantic. The most frequent polymers identified were PA, PE, and PET. Ingestion rates of microplastics varied between species and depth. Fishes ingested more microplastics in the upper mesopelagic layer.